Florid genital tuberculosis co-existing with adenomyosis and evading diagnosis - Thangappah, Radha B. P.; Meda, Sahitya; Tabassum, Roohi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
When tuberculosis affects genital organs of young females, the disease often remains silent or may present with symptoms which are common to other Gynaecological conditions as well. The diagnosis of genital tuberculosis is challenging and the diagnosis can be missed even with extensive investigations including molecular studies. A case of florid tuberculosis affecting the uterus, cervix, ovaries and tubes, co-existing with adenomyosis of the uterus and the cold abscess masquerading as bilateral ovarian endometriomas is reported.